Large-scale effects of offshore wind farms on seabirds of high conservation concern - Garthe, Stefan; Schwemmer, Henriette; Peschko, Verena; Markones, Nele; Müller, Sabine; Schwemmer, Philipp; Mercker, Moritz (Scientific reports, 2023)
The North Sea is a key area worldwide for the installation of offshore wind farms (OWFs). We analysed data from multiple sources to quantify the effects of OWFs on seabirds from the family Gaviidae (loons) in the German North Sea. The distribution and abundance of loons changed substantially from the period before to the period after OWF construction. Densities of loons were significantly reduced at distances of up to 9-12 km from the OWF footprints. Abundance declined by 94% within the OWF + 1 km zone and by 52% within the OWF + 10 km zone. The observed redistribution was a large-scale effect, with birds aggregating within the study area at large distances from the OWFs. Although renewable energies will be needed to provide a large share of our energy demands in the future, it is necessary to minimize the costs in terms of less-adaptable species, to avoid amplifying the biodiversity crisis.
Gesehen am 07.12.2023